Heterothallism and potential hybridization events inferred for twenty-two yellow morel species - Xi-Hui Du; Dongmei Wu; Heng Kang; Hanchen Wang; Nan Xu; Tingting Li; Keliang Chen (IMA Fungus)
Abstract Mating-type genes are central to sexual reproduction in ascomycete fungi and result in the establishment of reproductive barriers. Together with hybridization, they both play important roles in the evolution of fungi. Recently, potential hybridization events and MAT genes were separately found in the Elata Clade of Morchella. Herein, we characterized the MAT1–1-1 and MAT1–2-1 genes of twenty-two species in the Esculenta Clade, another main group in the genus Morchella, and proved heterothallism to be the predominant mating strategy among the twenty-two species tested. Ascospores of these species were multi-nuclear and had many mitochondrial nucleoids. The number of ascospore nuclei might be positively related with the species distribution range. Phylogenetic analyses of MAT1–1-1, MAT1–2-1, intergenic spacer (IGS), and partial histone acetyltransferase ELP3 (F1) were performed and compared with the species phylogeny framework derived from the ribosomal internal transcribed spacer region (ITS) and translation elongation factor 1-alpha (EF1-a) to evaluate their species delimitation ability and investigate potential hybridization events. Conflicting topologies among these genes genealogies and the species phylogeny were revealed and hybridization events were detected between several species. Different evolutionary patterns were suggested for MAT genes between the Esculenta and the Elata Clades. Complex evolutionary trajectories of MAT1–1-1, MAT1–2-1, F1 and IGS in the Esculenta Clade were highlighted. These findings contribute to a better understanding of the importance of hybridization and gene transfer in Morchella and especially for the appearance of reproductive modes during its evolutionary process.